Analysis of Passenger Car Equivalency (EMP) Values on Road Sections in BandarLampung City (Case Study: Ratu Dibalau Road Section and Damar Island Road Section) - Oktavia, Amelia; Michael, Michael; Maulana, Muhammad Irsal (Universitas Negeri Padang, 2024)
The increase in vehicle volume in Lampung Province has resulted in a decrease in road performance. Capacity evaluation is prevention, determining capacity there are several parameters, one of which is EMP. In this case, the analysis of road section performance refers to MKJI 1997. The characteristics of MKJI 1997 are strongly influenced by the traffic of major cities in Indonesia which are made the place of empirical research in 1991 - 1995. Of course, there are differences in the characteristics that occurred in that year with the current situation. This study was conducted to determine whether there is a difference in the EMP value in MKJI with the current field EMP. This research uses field survey data including traffic volume, road section geometry, and Time Headway data between vehicles. In this study, the emp value is analyzed using the Time Headway method and the data for analyzing the performance of road sections refers to the 1997 Indonesian Road Capacity Manual (MKJI). The results of the emp MC value for the morning and afternoon peak hours on Section 1 are 0.48 and 0.46. Section 2 is 0.46 and 0.44. This value is significantly different from the 1997 MKJI emp of 0.25. for the DS value using emp MKJI on section 1, the results are 0.45 and 0.68. for DS emp calculations on section 0,3 of 0,43 and 1. For section 2 DS emp MKJI of 0.33 and 0.48. For DS emp calculations on section 2 of 0,48 and 0,65. It can be seen that significant differences can be caused by traffic flow conditions, differences in road characteristics, road gemetry conditions, and environmental conditions in 1997 with current conditions. It can also be seen that the greater the emp value will affect the amount of traffic volume so as to make the degree of saturation value greater.